Factors on Quality of Life in Scizofrenia Patients - Afconneri, Yudistira; Puspita, Wulan Getra (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Schizophrenia is a mental disorder characterized by symptoms such as hallucinations and delusions. These symptoms can affect the quality of life in people with schizophrenia. From the data of Tanjung Paku Health Center, which suffers from schizophrenia as many as 46 people. The purpose of this study was to describe the life quality factors of schizophrenics in the working area of Tanjung Paku health center in Solok city in 2019. The purpose of this study was to describe the life quality factors of schizophrenics in the working area of Tanjung Paku health center in Solok city in 2019. This research is descriptive, carried out on June 11 to June 13, 2019 in the working area of Tanjung Paku Health Center, Solok City. The population in this study were all schizophrenic patients in the working area of Tanjung Paku Community Health Center in Solok City, amounting to 46 people. Sampling is done by means of total sampling totaling 25 people. Data is collected by means of observation and interviews, data processing is done by univariata analysis. The results of the study of 25 respondents found that most (56.0%) of respondents had poor physical health, most (68.8%) of respondents had bad social, most (56.0%) respondents had uncontrolled emotions, most of them (72%) respondents who can do activities well.